ON THE STARK BROADENING OF K III AND Ca IV SPECTRAL LINES - Dimitrijević, Milan S. (Bulletin of Natural Sciences Research, 2018)
Stark full widths at half maximum (FWHM) for ten multiplets of doubly charged potassium ion (K III), and 35 multiplets of triply charged calcium ion (Ca IV) have been calculated for electron density of 1017 cm-3 by using the symplified modified semiempirical (SMSE) method. The calculations were performed for temperatures from 5 000 K to 80 000 K, for K III and for temperatures from 10 000 K to 160 000 K for Ca IV, for broadening by collisions with electrons. The results obtained here will be implemented in the STARK-B database which is a memeber of Virtual atomic and molecular data center (VAMDC).